Sustainable Livestock Systems: What Role for the Private Sector? - Embree, S. (2025)
A presentation on the Elysium Brazil Cerrado Restoration Project, contributing to the panel on "Sustainable Livestock Systems. What Role for Private Sector?" organised by ILRI and partners on the project STELARR (Sustainable Large Scale Investments in Rangeland Restoration" at UNCCD CRIC 23, Panama City, December 1st 2025.